2013
DOI: 10.3389/fimmu.2013.00084
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin/Radixin/Moesin Proteins and Flotillins Cooperate to Promote Uropod Formation in T Cells

Abstract: T cell uropods are enriched in specific proteins including adhesion receptors such as P-selectin glycoprotein ligand-1 (PSGL-1), lipid raft-associated proteins such as flotillins and ezrin/radixin/moesin (ERM) proteins which associate with cholesterol-rich raft domains and anchor adhesion receptors to the actin cytoskeleton. Using dominant mutants and siRNA technology we have tested the interactions among these proteins and their role in shaping the T cell uropod. Expression of wild type (WT) ezrin-EGFP failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 42 publications
9
60
0
Order By: Relevance
“…It has been proposed that asymmetries in the strength of membrane-cortex attachment seems to be responsible in targeting the blebs to the cell's leading edge. In line with this, the expression level of the actin-membrane coupler ezrin (belongs to the ezrin-radixin-moesin (ERM) family) is elevated at the back of the Walker carcinosarcoma cells, which is consistent with the hypothesis that the membrane-to-cortex attachment is reduced at the cell's leading edge, supporting the bleb formation in this region (Martinelli et al, 2013;Rossy et al, 2007;Niggli and Rossy, 2008). It has turned out that an increase in the expression level or the activity of ERMs is correlated with reduced blebbing in zebrafish germ cells (Goudarzi et al, 2012), in A375 human melanoma cells (Lorentzen et al, 2011) and in mast cells (Yanase et al, 2011).…”
Section: Initiation Of Cellular Blebssupporting
confidence: 69%
“…It has been proposed that asymmetries in the strength of membrane-cortex attachment seems to be responsible in targeting the blebs to the cell's leading edge. In line with this, the expression level of the actin-membrane coupler ezrin (belongs to the ezrin-radixin-moesin (ERM) family) is elevated at the back of the Walker carcinosarcoma cells, which is consistent with the hypothesis that the membrane-to-cortex attachment is reduced at the cell's leading edge, supporting the bleb formation in this region (Martinelli et al, 2013;Rossy et al, 2007;Niggli and Rossy, 2008). It has turned out that an increase in the expression level or the activity of ERMs is correlated with reduced blebbing in zebrafish germ cells (Goudarzi et al, 2012), in A375 human melanoma cells (Lorentzen et al, 2011) and in mast cells (Yanase et al, 2011).…”
Section: Initiation Of Cellular Blebssupporting
confidence: 69%
“…Surprisingly, these glycoproteins also moved to uropods of chemokine-stimulated C1galt1 −/− neutrophils, even though, before stimulation, they did not copatch with GM1 in lipid rafts, and after stimulation, they remained in higher-density, detergent-soluble "nonraft" fractions. Uropods form through membrane interactions with flotillins 1 and 2 and with the actin cytoskeleton (54,55), in part through binding of ERM adaptors to the cytoplasmic domains of membrane glycoproteins (56). PSGL-1 associates with flotillins as measured by coimmunoprecipitation in detergent extracts and by a proximity-ligation assay in intact cells (31,57).…”
Section: Discussionmentioning
confidence: 99%
“…ERM proteins link membrane proteins to the actin cytoskeletal cortex (Fehon et al, 2010) and active phospho-ERM proteins localize to and regulate formation of the uropod in migrating lymphoblasts (Lee et al, 2004;Martinelli et al, 2013). We observed that the intensity of phospho-ERM labeling appeared to be reduced in shPrP-U937 cells (Fig.…”
Section: Prp Regulates Cell Shape and Migratory Behavior Of U937 Cellmentioning
confidence: 60%
“…ERM proteins are activated by phosphorylation of a conserved C-terminal threonine residue, which enables them to crosslink membrane receptors with the underlying actin cytoskeleton (Fehon et al, 2010). ERM protein activation is crucial for uropod formation (Ivetic and Ridley, 2004;Lee et al, 2004;Martinelli et al, 2013) and for β1-integrin-dependent T cell adhesion and polarization Liu et al, 2002). Therefore, the inhibition of ERM phosphorylation in the absence of PrP likely contributes to both the lack of uropods and the reduced β1 integrin adhesion observed for PrP-deficient monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation